The Process of Making Nata de Salacca from Honey Salak Fruit (Salacca edulis Reinw) with the Application of Biotechnology Techniques - Irwani, Anisa Novia; Auranina Oskandar, Yasmin; Novia Irwani, Anisa; Putri Rahmawati, Dian; Puri Ducha Rahmani, Tara (Journal of Biotechnology and Natural Science, 2021)
Salak is typical Indonesian fruit commonly found in tropical countries. This fruit can fill global fruit market via exports to various countries.  One of the varieties is "salak madu" ("honey salak"), whose scientific name is (Salacca edulis Reinw), which has higher economic value than "salak pondoh super". Some of the characteristics of honey salak are thick flesh, high water content, and sweet taste. Due to its high water content, honey salak rots quickly, resulting in useless waste and causing unfavorable smell. As such, utilization of overripe salak fruit (ripe close to rotten) can be done with implementation of biotechnological approach using Acetobacter xylinum to make nata. This study is aimed at utilizing overripe honey salak (ripe close to rotten) by processing it into Nata de salaca and identifying the factors affecting the production of Nata de salaca. The study used systematic review method by reviewing and examining previously published journal articles. The results of this study suggest that overripe salak can be utilized to make Nata de Salaca with the help of Acetobacter xylinum. Based on ratio of salak substrate to water, a good Nata has the ratio of 1 : 4. 1. Whereas, based on the factor of sprout extract additive material, it is  3%. Dan Whereas based on optimum duration of fermentation, it is 10 minutes.